Planning and Review Days on Participatory Integrated Climate Services for Agriculture (PICSA) Implementation in Dodoma and Arusha, Tanzania - Mwanga, Robert O.M.; Kisanga J; Dinh D (2016)
Since 2014, World Food Programme (WFP), CGIAR Research Program Climate Change Agriculture and Food Security (CCAFS), Tanzania Meteorological Agency (TMA) and University of Reading (UoR) have been hosting trainings of intermediaries and sharing climate information services. In Tanzania the trainings and climate related services have been offered to the three Global Framework for Climate Services (GFCS) pilot districts Kiteto, Longido and Kondoa, targeting the districts extension workers. These trainings and workshops aimed to equip stakeholders, particularly the intermediaries or extension workers, with the capacity to provide farmers with locally relevant climate, crop and livelihood information. As a part of follow up and monitoring, WFP, CCAFS and other partners on GFCS organized a three-day Planning and Review meetings in Dodoma (for Kiteto and Kondoa) and Arusha (for Longido) in November 2015. The purpose of this meeting was to assess the implementation plans since the first training of intermediaries that took place in 2014-2015. Plenary feedback from group works in Longido, Kondoa and Kitoto districts showed that trainings on Resource Allocation Maps (RAM), seasonal calendar, crop/livestock/livelihood options, participatory budget, and historical climate information, calculating probabilities and risks and seasonal forecast topics were successful, with farmers and pastoralists finding the topics relevant and useful. However, some logistical, cultural, linguistic challenges remain in training pastoralists and farmers, who need time to familiarize and understand the Participatory Integrated Climate Services for Agriculture (PICSA) approach that is very new to their community. Working groups concluded that although there were some challenges in implementing PICSA, about 935 farmers have been trained in Kondoa district, 1572 in Kiteto district, and 1453 in Longido district. Farmers have begun to make changes to their farming practices and share the information in village meetings and Ward Development Community meetings after receiving PICSA trainings.